Assessment Of Current Mining Strategy For Steep Reefs At Mine A - A. Nhasengo (The Southern African Institute of Mining and Metallurgy, 2007)
Paper written on project work carried out in partial fulfilment of B. sc. Eng (Mining Engineering) The purpose of this investigation was to assess the mining strategy for steep reefs at Mine A mine in 2005 and 2006. Reefs steeper than 35° were discovered when production commenced at the mine. At that time reefs steeper than 35° were not popular in South African tabular gold mines, therefore new techniques of mining them had to be developed. The underhand mining method was chosen for this purpose. The project was about assessing ventilation, support costs, local support cycles, adherence to the mine?s support standards, mine planning and efficiencies of the underhand mining method. The project work was covered by doing a literature research for underhand mining methods and performing a literature review of the mining methods, support methods, ventilation standards at Mine A. Underground visits were conducted at Mine A mine for data collection, and Mine B was visited to obtain information on support costs and efficiencies. During the investigation it was realized that the underhand mining method was an appropriate method for mining steep reefs; however, there were some challenges related to ventilation and support installation. Efficiencies could be realized with the underhand mining method and planning and scheduling were not different from breast mining.